Recoganisation and security guidance of data integrity in cloud storage - Sugumar, Ramalingam; S, Tamilenthi; Gopinath, K (International Multidisciplinary Research Journal, 2012)
Cloud computing has been envisioned as the de-facto solution to the rising storage costs of IT Enterprises. With the high costs of data storage devices as well as the rapid rate at which data is being generated it proves costly for enterprises or individual users to frequently update their hardware. Storage outsourcing of data to cloud storage helps such firms by reducing the costs of storage, maintenance and personnel. It can also assure a reliable storage of important data by keeping multiple copies of the data thereby reducing the chance of losing data by hardware failures. The study deal with the problem of implementing a protocol for obtaining a proof of data possession in the cloud sometimes referred to as Proof of irretrievability (POR). The problem tries to obtain and verify a proof that the data that is stored by a user at remote data storage in the cloud (called cloud storage archives or simply archives) is not modified by the archive and thereby the integrity of the data is assured. The verification systems prevent the cloud storage archives from misrepresenting or modifying the data stored at it without the consent of the data owner by using frequent checks on the storage archives.